Micro rheology of Jeffrey nanofluid through cilia beating subject to the surrounding temperature - Shaheen, Sidra; Maqbool, Khadija; Siddiqui, Abdul Majeed (Rheologica acta, 2020)
The objective of this study is to discuss the micro rheology of mucus (Jeffrey nanofluid) which is a complex biological fluid that protects lungs from pollutants, bacteria, and allergens that can be inhaled during the breathing process. To see the insight of pollutants and effect of surrounding temperature in the mucus, momentum, energy, and concentration equations are modeled with the help of metachronal wave formed by cilia beating. The governing system of equations are modeled in the wave and fixed frame and simplified by the lubrication approach. The velocity profile for recovery and effective stroke is compared and it is analyzed that effective stroke possess high magnitude of velocity when compared with the recovery stroke. The flow of mucus with pollutants and surrounding temperature is calculated with homotopy perturbation method and software “MATHEMATICA.” The results within the given domain are convergent under the different parameters appearing into the system of equations. The physical interpretation of involved parameters is explained through graphs.